Scientific and Systematic Approaches to Modeling of EFL Peer Learning in Higher Education - Makarova, Elena (JET (Journal of English Teaching), 2024)
The paper deals with EFL peer learning at a non-linguistic university. Lack of understanding of the mechanism of interactive learning as a system of relationships and interactions hinders creating the conditions for effective education. The aim of the study is to investigate theoretical and practical data on interactive learning, to design and describe the methodology for EFL peer learning in the form of educational models. The material includes basic postulates of constructivism, ecolinguistics, practice-oriented learning, peer learning and tutoring. Methods of modeling, experiment, observation and analysis are used. As a result, the structural components of interactive learning, their interconnections have been established and analyzed, the principles of interactive peer learning were formulated, including student activity; educational material selected in compliance with student’s knowledge; cyclical stages of a learning process; teacher’s preparatory work; classroom peer tutoring. Based on these principles, five models of peer learning have been designed each of which is centered around active interactions of students swapping the roles “tutor” - “tutee”. They are “Pair work”, “Group work”, “Peer assessment”, “Blended interactions”, “Extracurricular activities”. These models ensure maximum student involvement in EFL learning process, help increase motivation and level of language proficiency, develop students’ communication skills.